A short-term dynamical model for ghrelin. Issue 1 (July 2017) - Pires, J.G.; Borri, A.; De Gaetano, A.; Manes, C.; Palumbo, P.
Abstract: Ghrelin, a peptide hormone, occupies a crucial role in food intake control. Differently from other hormones contributing to energy homeostasis, usually exerting their regulating action by signaling satiety (e.g. leptin), ghrelin is known to stimulate appetite and, in general, to upsurge the propensity of animals to seek out food and start eating. Medical and experimental literature has shown that approximately 70-80% of ghrelin production occurs in the stomach, whilst the great part of ghrelin control, leading to ghrelin suppression soon after a meal administration, is exerted by signals originated in the small intestine. This note proposes a mathematical model for ghrelin dynamics, focusing the attention on its short-term 24 hours dynamics. The proposed model conforms to the established physiology by introducing a minimal multi-compartmental structure of the gastrointestinal tract. Model parameters are set in order to fit plasma ghrelin concentration data taken from the literature, related to an experiment in humans: simulation-based ghrelin predictions provide promising results if compared to real data. Besides to offer a proper description of the short-term ghrelin dynamics, the model can be thought of as a module of a bigger multi-compartmental structure, aiming to account for the "web of hormones" (including, e.g., leptin and insulin) related to food intake and energy homeostasis.